Strategi Marketing Berderma Melalui Crowdfunding di Akun Instagram @ikoy2an - Achmad, Zainal Abidin; Rahmawati, Icha Nur (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
Crowdfunding has now entered the world of marketing. The presence of a different crowdfunding concept through the ikoy-ikoyan game is a new thing in the realm of social media. Crowdfunding activities utilize Instagram social media by uploading campaigns in the form of videos and images on Instagram accounts. This study aims to find out the social media marketing strategy that has been carried out by Arief Muhammad in the @ikoy2an account. Using qualitative research methods and virtual ethnographic approaches. Researchers found that the ikoy-ikoyan trend has succeeded in shifting the giveaway trend that has developed in the last year. The ikoy-ikoyan trend has proven effective in increasing charity awareness, strengthening brand, customer engagement, and increasing the number of followers on Instagram accounts. Keywords: Crowdfunding, Marketing Strategy, Virtual Ethnography.